PENERAPAN STANDAR OPERASIONAL PROSEDUR PADA BISNIS COFFEE SHOP GARIS TANGAN - Devina Damayanti; Syafa Ramdila Laksana; Santi Pertiwi Hari Sandi; Dwi Epty Hidayaty (Jurnal Pijar, 2023)
Standard Operating Procedure is one of the stages or parts that must be carried out in all fields because this part is very important for the sustainability of operational processes and is also very useful for fulfilling and achieving desired targets. The purpose of this environment is to find out whether structured operational standards will facilitate business owners and employees in carrying out their tasks well and producing consistent product quality. The method used in visit was descriptive and qualitative methods. Data collection techniques, namely, using interview guides, literature studies, and documentation. The results of the visit showed that the implementation of standard operating procedures in Garis Tangan coffee shop business has been effective. From the planning of operational standards in Garis Tangan coffee shop business, it can be concluded that this visit was carried out to measure the effectiveness standard operating procedures in increasing the efficiency and consistency of business operations.